Group A streptococcus acute otitis media progressing to neuroinvasive disease in adults. (2018) - Patel, Kavin M.; Johnson, Jennie E.; Boxerman, Jerrold L.; Nau, Gerard J.
Abstract: Acute otitis media affects 700 million people each year with children being disproportionately affected relative to adults. Group A streptococcus is a pathogen implicated in a broad array of human pathology. It is, however, a rare cause of acute otitis media and neuroinvasive disease in older adults with only 2–3 cases occurring per year in the United States. We describe two such cases from a single institution in Rhode Island in 2017. The clinical presentation, neuroimaging and management are reviewed. The mechanism of intracranial spread may have involved dehiscence of the bony tegmen of the roof of the middle ear cavity.